Effects of Dexmedetomidine on motor- and somatosensory-evoked potentials in patients with thoracic spinal cord tumor: a randomized controlled trial. Issue 1 (December 2015) - Li, Yan; Meng, Lingzhong; Peng, Yuming; Qiao, Hui; Guo, Lanjun; Han, Ruquan; Gelb, Adrian
Abstract Background We hypothesized that the addition of dexmedetomidine in a clinically relevant dose to propofol-remifentanil anesthesia regimen does not exert an adverse effect on motor-evoked potentials (MEP) and somatosensory-evoked potentials (SSEP) in adult patients undergoing thoracic spinal cord tumor resection. Methods Seventy-one adult patients were randomized into three groups. Propofol group (n = 25): propofol-remifentanil regimenand the dosage was adjusted to maintain the bispectral index (BIS) between 40 and 50. DP adjusted group (n = 23): Dexmedetomidine (0.5 μg/kg loading dose infused over 10 min followed by a constant infusion of 0.5 μg/kg/h) was added to the propofol-remifentanil regimen and propofol was adjusted to maintain BIS between 40 and 50. DP unadjusted group (n = 23): Dexmedetomidine (administer as DP adjusted group) was added to the propofol-remifentanil regimen and propofol was not adjusted. All patients received MEP, SSEP and BIS monitoring. Results There were no significant changes in the amplitude and latency of MEP and SSEP among different groups (P > 0.05). The estimated propofol plasma concentration in DP adjusted group (2.7 ± 0.3 μg/ml) was significantly lower than in propofol group (3.1 ± 0.2 μg/ml) and DP unadjusted group (3.1 ± 0.2 μg/ml) (P = 0.000). BIS in DP unadjusted group (35 ± 5) was significantly lower than in propofol group (44 ± 3) (P = 0.000). Conclusions The addition of dexmedetomidine to propofol-remifentanil regimen does not exert an adverse effect on MEP and SSEP monitoring in adult patients undergoing thoracic spinal cord tumor resection. Trial registration The study was registered with the Chinese Clinical Trial Registry on January 31st, 2014. The reference number was ChiCTR-TRC-14004229.